Diagnosis and Management of Perforated Duodenal Ulcers following Roux-En-Y Gastric Bypass: A Report of Two Cases and a Review of the Literature - Mazen E. Iskandar; Fiona M. Chory; Elliot R. Goodman; Burton G. Surick (Case Reports in Surgery)
Perforated duodenal ulcers are rare complications seen after roux-en-Y gastric bypass (RYGP). They often present as a diagnostic dilemma as they rarely present with pneumoperitoneum on radiologic evaluation. There is no consensus as to the pathophysiology of these ulcers; however expeditious treatment is necessary. We present two patients with perforated duodenal ulcers and a distant history of RYGP who were successfully treated. Their individual surgical management is discussed as well as a literature review. We conclude that, in patients who present with acute abdominal pain and a history of RYGB, perforated ulcer needs to be very high in the differential diagnosis even in the absence of pneumoperitoneum. In these patients an early surgical exploration is paramount to help diagnose and treat these patients.